Optical properties of materials and their applications - Singh, Jai (Hoboken, NJ : John Wiley & Sons, 2020)
"Optical properties of a material change or affect the characteristics of light passing through it by modifying its propagation vector or intensity. Two of the most important optical properties are the refractive index n and the extinction coefficient K, which are generically called optical constants; though some authors include other optical coefficients within this terminology. The latter is related to the attenuation or absorption coefficient . In Part I, in this chapter, we present the complex refractive index, the frequency or wavelength dependence of n and K, so-called dispersion relations, how n and K are inter-related, and how n and K can be determined by studying the transmission as a function of wavelength through a thin film of the material"--
Previous edition: Optical properties of condensed matter and applications, 2006.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 23, 2020).
Keywords: Condensed matter -- Optical properties; Materials -- Optical properties; Electrooptics -- Materials; Condensed matter -- Optical properties; Electrooptics -- Materials; Materials -- Optical properties; Electronic books